Representing root physiological traits in the root economic space framework. Issue 3 (31st March 2022) - Yaffar, Daniela; Cabugao, Kristine G.; Meier, Ina C.
Abstract : This article is a Commentary on Han et al . (2022), 234 : 837–849 .